Answer:
3
Step-by-step explanation:
You calculate an answer by multiplying each side by each other. hope this helps.
Answer:
Choice A is the correct answer
Step-by-step explanation:
To evaluate the limits, we simply perform direct substitution; substitute -infinity into each expression in the alternatives and then simplify the expression. Notice that only the expressions in alternative A will fit this criteria since they will be tending to -infinity as x approaches -infinity.
8x2
20-8
3x4
Hope it helped
For this case we have the following points:
y = (- 2, 5)
z = (1, 3)
Therefore, the vector yz is given by:
yz = z - y = (1, 3) - (-2, 5)
yz = ((1 - (- 2)), (3-5))
yz = ((1 + 2), -2)
yz = (3, -2)
Then, the magnitude is given by:
lyzl = root ((3) ^ 2 + (-2) ^ 2)
lyzl = root (9 + 4)
lyzl = root (13)
Answer:
yz = (3, -2)
lyzl = root (13)
option A